Bilateral Pulmonary Embolism Following a Viper Envenomation in France: A Case Report and Review. Issue 19 (May 2016) - Bart, Géraldine; Pineau, Samuel; Biron, Charlotte; Connault, Jérôme; Artifoni, Mathieu
Abstract : Abstract: Complications following snake bites are not common in France. We report the case of a bilateral pulmonary embolism following a viper envenomation in France. A healthy 72-year-old female presented with a lower limb hematoma following a viper bite. She was admitted at the hospital 2 days later and received low-molecular-weight heparin because of bed rest. Seven days later, she complained of thoracic pain and respiratory failure, and a bilateral pulmonary was diagnosed, without biological sign of neither disseminated intravascular coagulation nor coagulation trouble. Repeated lower limbs Doppler ultrasound were normal. This case is particularly interesting because it is only the 7th reported case of pulmonary embolism following a snake envenomation; moreover, it happened in France where poisonous snakes are very rare. Several hypotheses have been made to explain this late localized coagulopathy: an increased level of unstable fibrin produced by thrombin-like glycoproteins from the venom is one of them.